The Prevalence and Associated Factors of Domestic Violence Against Pregnant Women During the COVID‐19 Pandemic: A Systematic Review and Meta‐Analysis - Kosar Miraei Mohammadi; Zohreh Shahhosseini; Mahtab Haji Mohammadreza; Fatemeh Heshmatnia; Roya Nikbakht; Erfan Ghasemi; Maryam Jafari; Hamed Milani; Marzieh Azizi (Brain and Behavior)
ABSTRACT Introduction Domestic violence (DV) against women has been reported increasingly, especially during the pandemic worldwide. Exposure to DV during pregnancy is associated with various maternal and neonatal adverse consequences. Therefore, the current study aims to systematically investigate and analyze the prevalence and associated factors of DV or intimate partner violence (IPV) against pregnant women during the COVID‐19 pandemic. Methods In this systematic review and meta‐analysis, systematic literature searches in electronic databases, including Google Scholar, PubMed, Web of Science, Scopus, ScienceDirect, and Scientific Information Database, were conducted from December 2023 to May 2024. Quality assessment of the included studies was performed using the Newcastle–Ottawa Scale for cross‐sectional and cohort studies. All included studies were entered into a meta‐analysis. The binomial distribution formula was used to calculate the variance of point prevalence. In addition, meta‐regression was used to assess the prevalence of DV based on the sampling place and quality of the included studies. All statistical analyses were performed with Stata version 11.0, Texas, USA. Results Of 16 studies included, 156,775 pregnant women participated, and the sample sizes varied from 215 to 77,310 individuals. According to the combining the results of 12 studies, the overall prevalence of physical, psychological, and sexual violence against pregnant women during COVID‐19 was estimated at 13.83 (95% CI, 5.92%–21.73%), 40.02% (95% CI, 22.74%–57.30%), and 15.09% (95% CI, 6.49%–23.69%), respectively. The pooled prevalence of the total IPV against pregnant women during COVID‐19, according to the combined results of 15 studies, was estimated at 36.82% (95% CI, 22.24%–51.40%). Conclusion Although the prevalence of all types of violence against pregnant women increased during the COVID‐19 pandemic compared to other times, the results of the present study indicated that psychological violence was the most common violence reported by pregnant women. Therefore, it seems that identifying high‐risk pregnant women as victims of violence is imperative to develop preventive interventions for this vulnerable group globally.